Propuesta para un sistema de tratamiento de agua potable para el acueducto Aguas del Trapiche S. A. S. en Villavicencio, Meta (2016)
For the realization of the degree proposed a system of treatment of pure water, for the aqueduct water of the Trapiche S.A.S in Villavicencio, Meta, from a well deep concession of his property, the company gave the initial characterization of the water, which was compared with current regulations, which highlighted four parameters that failed These amount of iron, colour, turbidity and free chlorine residual. The sum of these parameters with carried a high-risk index is not apt for human consumption. Based on these parameters, was a bibliographic comparison chart with pros, cons and applicability in order to evaluate the possible treatment options for these parameters in particular. We gave a percentage for the evaluation for any parameters which are very important to complete the Colombian rules, and important for the company.